Comparison Between the Calcium-Based Stabilizer and Non-Organic Agents on the Stabilization of Contaminated Soil - Fendi, Yaqeen M.; Saeed, Khitam A.; Sachit, Dawood E. (Salehan Institute of Higher Education, 2026)
This study was conducted to investigate the properties of nickel- and copper-contaminated soil and to determine the potential use of calcium stabilizers and inorganic agents as soil improvement methods. The soil was classified as loamy sand (SM) with a low plasticity index (PI = 4%), medium permeability, and high silica content (>33%). X-ray fluorescence (XRF) testing revealed nickel oxide concentrations of 1.5% and copper oxide concentrations of 2.5% in the soil. Nickel and copper contamination based on added nitrate salts was estimated at 1,500 ppm and 2,500 ppm, respectively. X-ray Diffraction (XRD) results showed that quartz and kaolinite were the most abundant, and the contaminants were likely present in an amorphous or surface-adsorbed manner. Unconfined Compressive Strength (UCS) results indicated a significant improvement in compressive strength: from 96 kPa (2% cement, 7 days) to over 12,445 kPa (7% cement, 28 days). The 20% fly ash yielded a strength of 934.5 kPa after 28 days, due to natural pozzolanic reaction and mineral adsorption. Overall, strength improved, and stability was achieved with increased curing time. These results demonstrate that cement and fly ash improved both the mechanical properties and environmental performance of sandy soils contaminated with heavy metals. However, the accelerated strength improvement for cement was significantly greater (over 12,445 kPa) than for fly ash (934.5 kPa, with 20% fly ash) after 28 days of curing. This result suggests that cement-based materials have superior load-bearing performance in applications, but fly ash may be less effective and potentially more environmentally friendly.